Application of quantitative and qualitative methods in the study of library activities in Bulgaria - Rusinova, Evgeniya (Qualitative and Quantitative Methods in Libraries, 2019)
The paper presents the main areas of application of quantitative and qualitative methods. It is shown the relationship between the agenda of the library area and the used research approaches. There are presented good practices in specific areas which are serving as a basis for full implementation of the qualitative and quantitative methods for evaluating the library activities. The library sector in Bulgaria is in a phase of complete transformation. This has a strong influence on the state of the research in the libraries. The priority activities are related with the modernizing of the library buildings, to attract different categories readers (children, pupils, students), the teaching of information literacy, the digitization of library collections. The study of library activities is focused mainly in a few areas: study of the general state of library system through analysis of the used new technologies; study of the professional realization of the graduated students in Library and Information Science university programs; analyzing the results of the programs of information literacy. In some university lectures at the Sofia Universiyt and SULSIT are presented also some aspects of the library research. In the specialized library periodicals are published, even occasionally, the information from surveys about the results of specific activities, conducted events about the attraction of readers, work with children and youth audience, the rate of introduction of new teaching methods and new educational disciplines and others. In the Bulgarian practice to assess the current state of libraries the most widespread method is the SWOT analysis.